2011
DOI: 10.1038/bjc.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD151 is a novel prognostic marker in poor outcome endometrial cancer

Abstract: Background:Type II cancers account for 10% of endometrial cancers but 50% of recurrence. Response rates to chemotherapy at recurrence are poor and better prognostic markers are needed to guide therapy. CD151 is a small transmembrane protein that regulates cell migration and facilitates cancer metastasis. High CD151 expression confers poor prognosis in breast, pancreatic and colorectal cancer. The prognostic significance of tetraspanin CD151 expression in poor outcome endometrial cancers was evaluated, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 42 publications
2
50
1
Order By: Relevance
“…Furthermore, the notion of CD151 as a tumor suppressor is supported by multiple clinical analyses of this molecule in several other types of human cancer, including bladder, endometrial and possibly colon cancer. [55][56][57] Hence, as a multi-faceted molecule, the functional role of CD151 during cancer development is likely linked to the cellular origin or oncogenic context of tumor-initiating cells as implicated for many adhesion molecules including integrins and their downstream effectors. [58][59][60][61] In summary, our current study demonstrates that tetraspanin CD151 contributes to the pubertal development of mammary glands by maintaining the normal activity of adult epithelial progenitor cells and ECM homeostasis.…”
Section: Implications For a Potential Role Of Cd151 In Human Breast Cmentioning
confidence: 99%
“…Furthermore, the notion of CD151 as a tumor suppressor is supported by multiple clinical analyses of this molecule in several other types of human cancer, including bladder, endometrial and possibly colon cancer. [55][56][57] Hence, as a multi-faceted molecule, the functional role of CD151 during cancer development is likely linked to the cellular origin or oncogenic context of tumor-initiating cells as implicated for many adhesion molecules including integrins and their downstream effectors. [58][59][60][61] In summary, our current study demonstrates that tetraspanin CD151 contributes to the pubertal development of mammary glands by maintaining the normal activity of adult epithelial progenitor cells and ECM homeostasis.…”
Section: Implications For a Potential Role Of Cd151 In Human Breast Cmentioning
confidence: 99%
“…7,8) has been shown in clinical studies to have a positive correlation with poorer patient outcomes in a variety of cancers including prostate (9), lung (10), colon (11), breast (12,13), renal (14) and endometrial cancers (15). Molecular studies involving CD151 with cancer progression and metastasis to date have focused on in vitro and grafting models.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies have reported significantly higher CD151 expression in triple negative endometrial cancer as compared to other histological types. Increased CD151 expression is the basis for worse prognosis [15]. Likewise, higher CD151 expression in triple negative breast cancer is associated with shorter survival time and poorer prognosis [32].…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, only 4 papers have dealt with triple negative EC [13][14][15][16].…”
mentioning
confidence: 99%